Investment Feasibility Analysis for Sustainable Capacity Expansion of Aircraft MRO in Indonesia - Davirza, Puri Alodia; Nainggolan, Yunieta Anny (Integrasi Sains Media, 2025)
According to global market outlooks, the aviation industry is expected to demand 43,975 new aircraft between 2024 until 2043, which will significantly increase the need for Maintenance, Repair, and Overhaul (MRO) services. As the leading MRO provider in Indonesia, Aeroantara Technic is well positioned to capture this growth. However, it faces internal challenges due to its prolonged negative equity position. This study assesses the investment feasibility of an investor to develop a new wide body aircraft hangar with two to four additional slots that would be operated by Aeroantara Technic under an Operation Management (OM) scheme. The analysis is approached from two perspectives. First, whether the project is financially viable for the investor since without a feasible investment return, Aeroantara Technic would not be able to lease the hangar. Second, if the project is indeed feasible, the study estimates the potential benefit that Aeroantara Technic could gain from operating the hangar under this arrangement. The analysis integrates financial data projections using discounted cash flow modelling, supported by publicly available data inputs from industry and internal insights utilized to build credible assumptions and enhance the realism of projections. The results indicate a robust return on investment with a positive NPV of USD 19.2 million, an IRR of 14.2%, and payback period 10.6 years, confirming adequate profitability and feasibility. To further account of uncertainties, a sensitivity analysis using Monte Carlo simulation is conducted, strengthening the confidence in the project decision under varying risk scenarios. Align with international aviation sustainability goals (ICAO’s CORSIA and IATA’s Fly Net Zero), Aeroantara Technic could incorporating ESG aspects that may unlock green financing, government incentive, and customer preference for sustainable MROs. In conclusion, expanding Aeroantara Technic’s capacity for aircraft maintenance through a new hangar represents a financially sound strategic move aligned with the industry growth forecasts.